Association between life’s essential 8 score and the risk of abdominal aortic aneurysm: a prospective cohort study from UK Biobank data - Sixu Chen; Zegui Huang; Dachuan Guo; Chang Guan; Zhiteng Chen; Tingfeng Chen; Haifeng Zhang; Yangxin Chen; Jingfeng Wang (BMC Public Health)
Abstract Background The healthy lifestyle factors have been closely associated with the risk of abdominal aortic aneurysm. The American Heart Association (AHA) recently released a checklist of health factors known as Life’s Essential 8 (LE8) to optimize cardiovascular health. The aim of this study was to test the hypothesis that greater adherence to the LE8 score was associated with a decreased risk of new-onset abdominal aortic aneurysm (AAA). Methods This study included 279,251 UK Biobank participants without a history of AAA. LE8 score was calculated using 8 metrics according to the AHA’s definition, and the study population was divided into four groups based on LE8 quartile. The Cox proportional hazard model was used to assess the association between LE8 score and risk of AAA. Results During a median follow-up of 12.77 years, 1042 cases of incident AAA were identified. After adjustment for potential confounders, the hazard ratio (95% confidence interval) of AAA was 0.52 (0.43, 0.64) for the Q2 group, 0.39 (0.32, 0.49) for the Q3 group, and 0.20 (0.12, 0.28) for the Q4 group, when compared with the Q1 group (the lowest LE8 score). When analyzed as a continuous variable, each 5-point increase in LE8 score was associated with a 20% lower risk of AAA. The association between LE8 score and risk of AAA remained robust after sensitivity and subgroup analyses. Conclusion Higher LE8 score was associated with lower risk of AAA in the general population, emphasizing the importance of maintaining a healthy lifestyle to prevent AAA.